Hubungan Peran Pengawas Menelan Obat Dengan Kepatuhan Minum Obat Penderita Tuberkulosis Di Puskesmas Sukarahayu - Miranda, Elfa Dhela; Adiutama, Novian Mahayu; Ningrum, Dwi Agustia (Poltekkes Kemenkes Bengkulu, 2025)
Tuberculosis (TB) remains a health challenge in Indonesia. Its treatment is lengthy and requires discipline, making medication adherence crucial. One way to improve adherence is through the involvement of Medication Supervisors (PMO) during treatment. To examine the relationship between the role of PMO and the level of medication adherence among pulmonary TB patients at Puskesmas Sukarahayu. This study used a quantitative approach with a cross-sectional design and purposive sampling, involving 135 TB patients. Data were collected via questionnaires on the role of PMO and MMAS-8, then analyzed using Spearman's Rank test. The study showed that the majority of respondents had PMOs who played a supportive role (94.8%), and most respondents were adherent to their medication (63.7%). The statistical analysis indicated a significant relationship between the role of PMO and medication adherence (p = 0.000) with a correlation coefficient r = 0.638, indicating a strong and positive relationship. The better the PMO role, the higher the adherence of TB patients to treatment. Improving the quality and engagement of PMOs is an effective strategy to reduce dropout rates, prevent resistance (DR-TB), and accelerate recovery. This confirms the importance of training and support for PMOs in TB control programs.